Morfoanatomia, atividade anti-inflamatória e parâmetros bioquímicos de Poiretia tetraphylla (Poiret) Burkart (leguminosae) - Royer, Lauri Antônio Junior (2011)
Poiretia tetraphylla (Poir.) Burk., is part of Leguminosae family, Papilionoideae subfamily. It is popularly known as erva-de-touro-miúda or chá-dos-pampas and occurs in Brazil, Argentine, Paraguay and Uruguay. P. tetraphylla is used in traditional medicine as tonic, sudoriferous, in stomach disorder, anti-inflammatory, anthelmintic and insecticidal. This plant is an erect herb to sub-shrub that can achieve 1meter tall. Its inflorescence is terminal, raceme shaped, with yellow flowers. Its fruits are samara type up to 2,5 cm length. Was verified the presence of volatile oil, tannins, flavonoids, and saponine in your leaves, stem and flowers. The morphological analysis was made by means of a stereomicroscop and the anatomical analysis in paradermic and transversal sections was made with hydroxide ethyl methacrylate inclusion. A pharmacobotanical study lead shows that leaves are characteristically 4-leaflets, the leaflets present themselves with 0,5 to 1,2 cm length and 0,5 to 1 cm wide and obovate shape. Has cuticle plain and plicate, stomata are present in both epidermal faces, mucilaginous cells and does not present epicuticular formations. The mesophyll is heterogeneous of dorsiventral type and the vascular bundles are of closed collateral type. In distal region occurs secretory cells of rounded shape with bright content in bluish-green tint. The stem can reach up to 1 meter high and 0,15 to 0,40 cm in diameter, and is characteristically angular, striate, glabrous, greenish, slightly branched at the base and with abundant oblong and translucent glands. The stem epidermis present itself uniestratified, with thick cuticle, stomata are very pronounced, rounded mucilaginous glandular formations with internal content bluish and does not present trichomes. The cortex is formed by 1-5 layers of parenchyma cells with different sizes, the phloem is protected by, a group of up to six layers of sclerenchyma fibers which present themselves as an interrupted ring surrounding the vascular system. The central cylinder characterized the sifonestelic continuous ectofolic type. The pith is composed of parenchyma cells with the intercellular space of meatus type, and does not present any internal content. These morphoanatomical singularities are important and relevant in pharmacobotanical works, because together, can be used in authenticity from various vegetal species. Anti-inflammatory activity of water-ethanol extract of Poiretia tetraphylla in a model of induction of formation of granulomatous tissue in rats and also hepatic and renal toxicity through serum dosage were evaluated. After treatment period, the animal group treated with P. tetraphylla showed an inhibitory inflammation process of 31,20±4,71%, while the nimesulide group, the pattern, obtained an inhibitory inflammation process of 21,42±6,52%, when compared to negative control 20% of propylene glycol (p<0,05). The serum levels of AST, ALT and creatinine in all groups of animals, do not shown significant elevation when compared to negative control. Anti-inflammatory activity exhibited for P. tetraphylla could be associated to his composition which contains saponines and flavonoids.